Spiritual counsel in the Anglican tradition - Hein, David, 1954-; Henery, Charles R. (James Clarke & Co., 2010)
As the world grows increasingly complex, as society becomes more and more fractured, as from day to day and even moment to moment basic attitudes and convictions shake and personal loyalties shift, human beings need more, not less, good counsel for Christian living. This book reaches into the treasury of Anglican spirituality and draws out pearls of wisdom for today's needs. Here the reader will discover spiritual guides - both clergy and laity - who speak directly to their own hearts, minds, and souls. The Anglican tradition has shown an abiding concern for a holy living that leads to a holy.